2019
DOI: 10.3390/mi10060361
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Al Incorporation into HfO2 Dielectric by Atomic Layer Deposition

Abstract: This study presents the characteristics of HfAlO films for a series of Al incorporation ratios into a HfO2 dielectric by atomic layer deposition on a Si substrate. A small amount of Al doping into the HfO2 film can stabilize the tetragonal phase of the HfO2, which helps to achieve a higher dielectric constant (k) and lower leakage current density, as well as a higher breakdown voltage than HfO2 film on its own. Moreover, assimilation of Al2O3 into HfO2 can reduce the hysteresis width and frequency dispersion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…The aggressive scaling of the equivalent oxide thickness (EOT) of metal–oxide–semiconductor field-effect transistors (MOSFETs) for achieving sophisticated device speeds and minimal power consumption has made SiO 2 obsolete as an insulating material [ 1 , 2 , 3 ]. As a result, oxide materials, which have a high dielectric constant ( k ), have emerged as the most suitable alternatives from the viewpoint of the realization of faster devices and overcoming the high leakage current problem [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aggressive scaling of the equivalent oxide thickness (EOT) of metal–oxide–semiconductor field-effect transistors (MOSFETs) for achieving sophisticated device speeds and minimal power consumption has made SiO 2 obsolete as an insulating material [ 1 , 2 , 3 ]. As a result, oxide materials, which have a high dielectric constant ( k ), have emerged as the most suitable alternatives from the viewpoint of the realization of faster devices and overcoming the high leakage current problem [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aggressive scaling of the equivalent oxide thickness (EOT) of metal–oxide–semiconductor field-effect transistors (MOSFETs) for achieving sophisticated device speeds and minimal power consumption has made SiO 2 obsolete as an insulating material [ 1 , 2 , 3 ]. As a result, oxide materials, which have a high dielectric constant ( k ), have emerged as the most suitable alternatives from the viewpoint of the realization of faster devices and overcoming the high leakage current problem [ 2 , 4 , 5 ]. Although many studies have reported several candidate high- k dielectric materials, Al 2 O 3 has attracted attention as the most desirable of such materials, predominantly because of its comparatively larger band gap (which provides a better band alignment with the channel material), better thermal solidity, lower oxygen and ionic transportation, and more effective inactivation of interface traps in the channel material [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As potential gate insulator candidates in III-V channel material-based nano-metric metal oxide semiconductor field-effect transistors (MOSFETs), which are considered as a future device for logic applications with a higher speed and bottled-up power consumption, the most studied Hf and Zr-based high-k oxides suffer from a lower barrier elevation as well as a destitute interface with the semiconductor material compared to the SiO 2 /Si-based system. These shortcomings are hindrances to achieving the leakage current challenge [1][2][3][4][5]. To solve these issues, an interfacial layer of Al 2 O 3 is added between the above-mentioned dielectric materials and semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional interface trap model is unable to explain the border trap behavior due to a time constant mismatch between both types of traps, as well as the border trap estimation from capacitance-voltage (C-V) hysteresis, which suffers from complete re-emission of captured charge at the C-V reverse sweep. Consequently, it is appropriate to characterize these traps by regarding accumulation frequency dispersion [3,17]. Furthermore, there are already several reports regarding border trap reduction by following some annealing process, although a clear understanding of the annealing ambient is lacking [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…We also find that the small variation on hysteresis windows of 9%‐ and 12%‐Al‐doped devices are associated with reduced oxygen vacancies or defects in gate stack due to high‐content Al doping . Although the Al doping into HfO 2 can effectively reduce the defects traps and improve leakage current, it also brings the issue of strong antiferroelectric property affecting the magnitude of 2 P r . Based on our experimental results shown in Figure b, we can observe that 9%‐Al‐doped devices exhibit a correspondingly large and stable hysteresis window under various irradiation doses, which confirms that the higher Al‐doping concentration is beneficial for enhancing the resistant to radiation exposure.…”
mentioning
confidence: 99%